Correlation between Macular Non-Perfusion and Patterns of Corresponding Retinal Layers in Diabetic Patients - Sherif Ahmed Shawky (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: Diabetic retinopathy is a common deficiency of diabetes mellitus. Diabetic macular ischemia [DMI] is a permanent form of diabetic maculopathy, and its presence reduces the potential benefits of diabetic retinopathy management. Optical coherence tomography [OCT] is used to precisely and reliably measure the macular thickness and outline the retinal layers. Optical coherence tomography angiography [OCTA] can be utilized as a reliable tool to classify the superficial capillary plexus [SCP], the deep capillary plexus [DCP] and the capillary non-perfusion [NP]. Aim of the work: The current research aimed to investigate the correlation between macular non-perfusion that diagnosed by OCTA and patterns of macular layers that diagnosed by OCT scans through the same parts, in a trial to help in the evaluation of both structural and vascular integrity. Patients and Methods: The study included 250 eyes of 125 diabetic patients. All study participants were scanned by OCTA. OCT angiograms were re-sampled with OCT scans from the same region, permitting synchronous evaluation of structure and blood flow. Results: 250 of 125 diabetic patients were categorized into two groups according to capillary NP, ischemic [G1] and non-ischemic [G2]. In current study the incidence of DMI was 40%. The incidence of DCPNP was 100% in eyes with DMI while the incidence of SCPNP was 71%. The incidence of foveal avascular zone [FAZ] irregularity, disorganization of the retinal inner layers [DRIL], inner/outer segment IS/OS and external limiting membrane ELM disruptions were 100%, 83%, 95%, 71% respectively among eyes with DMI. DCPNP was more found in all eyes with FAZ irregularity, DRIL, IS/OS and ELM disruption than SCP NP which makes it as the central cause of structural changes in the retina during ischemia. There was a strong positive correlation between the appearance of FAZ irregularity, DRIL, IS/OS and ELM disruption with each of the duration and severity of DR. Conclusion: FAZ irregularity, DRIL, IS/OS and ELM disruption are considered reliable OCT/OCTA findings that reflect an underling DMI and their existence can influence the visual prognosis.